Drosera quartzicola (Droseraceae), a new and threatened species from the Serra do Cipó, Brazil - Rivadavia, Fernando; Gonella, Paulo Minatel (Phytotaxa, 2011)
Drosera quartzicola (Droseraceae), a new species from the Serra do Cipó highlands, Minas Gerais state, southeastern Brazil, is described here. The morphological characters that distinguish it from similar Drosera species are discussed, together with habitat information, detailed illustrations, and its conservation status. A key to the Drosera species of the Serra do Cipó is provided.